Seamless care, safe care : the challenges of interoperability and patient safety in health care : proceedings of the EFMI Special Topic Conference, June 2-4, 2010, Reykjavik, Iceland - Blobel, Bernd; Hvannberg, Ebba T.; Valgerđur Gunnarsdóttir (Studies in health technology and informatics ;, 2010)
This book contains the proceedings of the Tenth European Federation for Medical Informatics (EFMI) Special Topic Conference 2010; Europe's leading forum for presenting the results of current scientific work in health informatics processes, systems and technologies. Included are two invited keynotes, one session keynote and 25 full papers, selected by the Scientific Programme Committee from 61 submissions, each rigorously reviewed by three reviewers. Subjects include: Electronic health records and persona health records, traceability, security, privacy and safety and quality, as well as interoperability and standards, patient empowerment, satisfaction and safety, continuity of care and device integration. Most of the topics are interdisciplinary in natur and the book will be of interest not only to those scientists involved with medical, bio- and health informatics, but to all health administrators, medical professionals and representatives of industry and consultancy in the various health fields.